Upper and Lower Continuous Multifunctions Defined between an Ideal Topological Space and a Bitopological Space (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from an ideal topological space into a bitopological space, called upper $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower $τ^\star(σ_1,σ_2)$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper $τ^\star(σ_1,σ_2)$-continuous multifunctions and lower$τ^\star(σ_1,σ_2)$-continuous multifunctions are investigated.